The Role of Context in Language Development for Children With Autism Spectrum Disorder - Sánchez Pérez, Patricia; Nordahl-Hansen, Anders; Kaale, Anett (Frontiers in Psychology, 2020)
Parent and preschool teacher ratings of the 10 noun categories of MacArthur-Bates Communication Development Inventory (CDI) were used to study expressive language in 2-4-year-old children with autism spectrum disorder (N=58) across the home and preschool context. There was no significant difference in the total number of words the children said in the two contexts, but the children said significantly more words in the noun categories “Furniture and rooms” and “People” at home. Only one third of the words the children said were said both at home and in the preschool, while the other two thirds were said only at home or in the preschool. This suggests that what words the children use across contexts differ substantially and that their vocabulary is larger than it seems when measured only in one context. This novel study highlights the importance of assessing the language in children with autism spectrum disorder in multiple contexts in order to better measure their vocabulary and to design appropriate language interventions.